Dogsong - Paulsen, Gary (Bradbury Press, 1985)
A fourteen-year-old Eskimo boy who feels at odds with aspects of modern life takes a 1400-mile journey by dog sled across ice, tundra, and mountains seeking his own "song" of himself.